Paradigms and paradoxes in the metamorphosis of ecotourism - Loredana, dragomir; Mazilu, Mirela (Quaestiones Geographicae, 2021)
In 2020 and 2021, the entire evolution of human society is under the sign of a paradox, of the adversity of events, coming in avalanche. The tourist evolutions themselves suffer the imprint of the paradox. These paradoxes urgently require new paradigms, the famous ‘paradigm shifts’, mentality, optics, action. The purpose of this research is to outline the main aspects of the research problem and diagnose the situation, with focus on identifying hypotheses for future descriptive or causal research as well as to explore the reasons, attitudes and values of the paradigm and paradox, which differentiate the two notions approached: testing new concepts of forecasting, a product specific to the destination under analysis and in identifying other viable, sustainable alternatives and their analysis in parallel with modelling and promoting new ideas of tourism products or services, respectively improving the existing ones. This article aims to capitalise on the paradox, already successfully applied in economics by the author of the method and in shaping and delimiting ecotourism (in particular the ecotourism from the destination Țara Hațegului – Retezat), emphasising the role of self-contradiction of the field, through a specific type of economic reasoning, in which the rapid evolution of tourism risks are becoming its own cause of its disappearance, knowing that too much tourism kills tourism. Responsibility and the mesological spirit are the only ways to counteract the paradox phenomenon, even a paradigm in the metamorphosis of ecotourism.